Addition of garlic (Allium sativum) and onion (Allium cepa) in the diet on productive parameters in broiler chickens - Velásquez Vergara, Carlomagno Ronald (2021)
The intensive use of growth-promoting antibiotics (APC) has led to bacterial resistance with harmful effects on health, in this situation it is necessary to look for alternative products, such as phyt1ogenic products. The objective of the research was to evaluate the effect of garlic and onion flour in the diet on productive performance and batch uniformity in broilers. 150 male beef chickens of the Cobb 500 line were used. The broilers were randomly distributed into three groups with five replications and each replication with ten chickens. The treatments were: T0: Negative control, without APC; T1: Positive control, with APC (Enramycin 8%); T2: Garlic flour 0.75% + onion 0.75%. The productive performance variables were: live weight, feed consumption, feed conversion and batch uniformity. The analysis of variance of a completely randomized design (DCA) and the Tukey test were used to evaluate the variables studied. No significant differences (P> 0.05) were found in the productive performance, when comparing the treatment of garlic and onion flour (T2) with the treatments without APC (T0) and with APC (T1); batch uniformity was high, without showing differences (P> 0.05) between treatments. Garlic and onion flour could be an alternative for use in the diet of broilers.